Design and implementation of La Salle University Payroll System - Luy, Luisander C. (Lasallian Research Forum, 2009)
The study focuses on the Payroll System of La Salle University, Ozamiz City, it will take ito account the college and integrated school faculty, staff and maintenance only. Other transactions that are beyond the scope mentioned are no longer part of the study. Moreover, this study is a preliminary process in improving the payroll system. The investigation made use of the descriptive method of research through interview, questionnaires and content analysis of documents. The study was conducted at La Salle University, Ozamiz City. The data of this investigation was gathered from the payroll-in-charge. La Salle University uses a computerized payroll process limiting to some degree such as in computing the fixed deductions like Withholding Tax, Social Security System, Pag-ibig Contribution, Philhealth/Medicare. The computation of the actual salary based on the faculty load per semester, extra load, variable deductions, 13th month salary and honorarium are all inputted to the system. With this, the payroll process does not fully utilize the extent to which computers are capable of. The existing reports generated by the payroll system are limited to some extent. The existing payroll system must be enhanced to maximize the use of the computers. Thus, allowing payroll clerks to be more productive. With the findings of the study, it is recommended that payroll system be enhanced. It further suggests the following improvements: the automation of the daily time record using the biometric technology for staff, the use biometric technology will then be embedded into the payroll system and the payroll system be onlined.